THE PERSPECTIVES OF ISLAMIC SCHOLARS ON RELIGIOUS DERADICALIZATION AND SOCIAL MEDIA ROLES - M Nurul Ikhsan Saleh; Yuli Astiana (Akademika : Jurnal Pemikiran Islam, 2021)
Tackling religious radicalism is a challenge in Indonesia which acts of intolerance, group exclusion, religion-based violence, terrorism, and hate speech through social media occur repeatedly. This study aims to explore the perceptions of Islamic scholars in Yogyakarta regarding the deradicalization of religion and the role of social media in religious deradicalization. This research uses a case study method which is part of qualitative research. Researchers collected data by conducting in-depth interviews via offline or online interviews through the Zoom application. Participants were 16 male and female Islamic scholars coming from various backgrounds of Islamic organizations, such as Muhammadiyah, Nahdlatul Ulama, the Indonesian Islamic Da’wah Institute, Hizbut Tahrir Indonesia, and the Qur’an Tafsir Council. The location of this research is Yogyakarta Special Region. Interview data were analyzed using thematic analysis methods. This study of religious deradicalization found four major themes, namely strengthening awareness of being Indonesia, prioritizing an inclusive approach as a soft approach in fighting radicalism, promoting a deep understanding of Islam, and utilizing social media. This research provides a novel finding that could contribute to the government, religious leaders, educational institutions, and The National Counter Terrorism Agency where religious deradicalization programs need to be focused on a soft approach, involving the use of social media, targeting blind spot areas such as study programs of medical, engineering, and pharmacy at universities and ensuring mosques uncontrolled by radical groups.